EFEKTIFITAS PENGGUNAAN METODE PEMBELAJARAN ELEARNING BERBASIS BROWSER BASED TRAINING TERHADAP PRESTASI BELAJAR SISWA PADA KOMPETENSI PEMELIHARAAN/SERVIS TRANSMISI MANUAL DAN KOMPONEN - Bisri, Khasan; Samsudi, -; Supraptono, - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2009)
The research type applied by this was experiment which truth/eksperimen isreally with pattern randomized control-group pretest-posttest design, while focusingresearch in this final project is knowing the effectiveness result of student learning afterusing E-Learning study method bases on Browser Based Training at KompetensiPemeliharaan/servis Transmisi Manual and Komponen. The place of his research is inExpertise Program Teknik Mekanik Otomotif SMK Negeri 2 Kendal. The collecting datamethods are documentation and test method. The study method of this Browser BasedTraining has been tested to one class as an experiment class, while for control class byusing conventional method which has been tested to one class from Expertise ProgramTeknik Mekanik Otomotif in SMK Negeri 2 Kendal. Based on result of the research, theconclusion is the result improvement of student learning at KompetensiPemeliharaan/Servis Transmisi Manual and Komponen by using better MetodePembelajaran Browser Based Training better than applying conventional method.Keywords: E-Learning, Browser Based Training.